Innovación e incumbent failure: Una ilustración usando la industria de las telecomunicaciones en Colombia (2008)
This paper provides an analysis of the determinants of the Incumbent failure arising from the interdependence competitive. It is used tools provided by game theory (backward induction and analysis of joint strategies in games of signaling) for determining the incentives to invest in innovation for an incumbent firm. For illustration purposes, the case of Telecom and the entry of mobile cellular in Colombia is used. We conclude that participation in the existing market and the expected magnitude of demand that will remain old technology, are barriers to set a firm decides to invest in innovation. The probability of an incumbent firm to invest in innovation is inverse to the likelihood of success of the entrant, the amount of such investment and the magnitude of the benefits that would accrue from the firm established its current product, if the entrant is successful.